Effects of Lime-Based Waste Materials on Immobilization and Phytoavailability of Cadmium and Lead in Contaminated Soil - Lim, Jung Eun; Ahmad, Mahtab; Lee, Sang Soo; Shope, Christopher L.; Hashimoto, Yohey; Kim, Kwon-Rae; Usman, Adel R. A.; Yang, Jae E.; Ok, Yong Sik (Clean : soil, air, water, 2013)
Low cost lime‐based waste materials have recently been used to immobilize metals in contaminated soils. This study was conducted to evaluate the effects of oyster shells and eggshells as lime‐based waste materials on immobilization of cadmium (Cd) and lead (Pb) in contaminated soil, as well as their effects on metal availability to maize plants (Zea mays L.). Oyster shells and eggshells were applied to soils at 1 and 5% w/w, after which they were subject to 420 days of incubation. The toxicity characteristic leaching procedure (TCLP) test was employed to determine the mobility of Cd and Pb in soils. The results showed that the addition of waste materials effectively reduced the metal mobility as indicated by the decrease in the concentration of TCLP‐extractable Cd and Pb, and this was mainly due to significant increases in soil pH (from 6.74 in untreated soil to 7.85–8.13 in treated soil). A sequential extraction indicated that the addition of such alkaline wastes induced a significant decline in the concentration of Cd in the exchangeable fraction (from 23.64% in untreated soil to 1.90–3.81% in treated soil), but it increased the concentration of Cd in the carbonate fraction (from 19.59% in untreated soil to 36.66–46.36% in treated soil). In the case of Pb, the exchangeable fraction was also reduced (from 0.67% in untreated soil to 0.00–0.01% in treated soil), and the fraction of Pb bound to carbonate was slightly increased (from 16.61% in untreated soil to 16.41–18.25% in treated soil). Phytoavailability tests indicated that the metal concentrations in the shoots of maize plant were reduced by 63.39–77.29% for Cd and by 47.34–75.95% for Pb in the amended soils, with no significant differences being observed for the amendment types and the application rates. Overall, these results indicate that oyster shells and eggshells can be used as low cost lime‐based amendments for immobilizing Cd and Pb in contaminated soils. Oyster shells and eggshells can be used as low cost lime‐based amendments for immobilizing cadmium and lead in contaminated soils. TCLP test showed that the addition of waste materials effectively reduced the metal mobility. Phytoavailability tests indicated that the metal concentration in the shoots of maize plant was also reduced.